Bionomics and Management of Maize Weevil, Sitophilus zeamais Motschulsky - Paneru, Ram B.; Thapa, Resham B.; Sharma, Prem N.; Sherchan, Dil P.; GC, Yubak D. (Journal of the Plant Protection Society, 2018)
The maize weevil Sitophilus zeamais Motschulsky (Coleoptera:Curculionidae) is an important pest of maize in storage in term of losses caused in food quality and quantity in Nepal. Attempt made to review bionomics and management practices of this pest gleaning published literatures/papers on national and international journals, proceedings, reports, newsletter and books. The paper discusses on nomenclature, morphology, distribution, biology and ecology of maize weevil and provides prospect of using various physical, sanitary, cultural, botanical, biological and chemical control measures to manage weevil. This information is useful to personnel involved on agricultural research and development for developing location specific integrated pest management approach of this pest. Finally, it also shows importance of farmers’ awareness on pest biology and ecology, appropriate maize harvesting time, storage structures and post-harvest handling practices to reduce losses in maize storage.